A Note on the Departmental Cultivation, Collection and Curing of Cardamoms in the Evergreen Forests of Madras Presidency - Khan, A. H. (Indian Forester, 1944)
The method of propagation of wild cardamons in evergreen forests, and the technique of raising new plantations in suitable areas are described with figures of cost and yield. Hints on collection, curing and storage with a description and sketch of a cardamom drying kiln are given.